University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 5 - Practice Exercises - Page 342: 18



Work Step by Step

Since, we have $ x^3+\sqrt y=1$ $\implies y=(1-x^3)^2=x^6-2x^3+1$ We know that $\int x^{n} dx=\dfrac{x^{n+1}}{n+1}+C$ where $C$ is a constant of proportionality. $\int_0^1 x^6-2x^3+1 dx=[\dfrac{x^7}{7}-2x^4/4+x]_0^1$ or, $=(\dfrac{1}{7}-0)-2(\dfrac{1}{4}-0)+(1-0)$ or $=\dfrac{9}{14}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.